Answer:
4
Step-by-step explanation:
It's ok! This is simple. Simply plug in your given values. Since g(x) = -1, plug that into the equation.
g(x) = -x + 3
g(-1) = -(-1) + 3
=1+3
=4
Answer:
C. since 8, 15, 17 are pythagorean triples
<em>when we solve the equation it will become
x</em>² + 9x<em>= 0
now here a = 1 , b = 9 and c = 0
by using quaderatic formula
x = -b +,-</em>√<em>b </em>²<em>- 4ac / 2a ( 2a is divided by all terms )
by putting values
x = - 9 +,</em><em>- </em>√<em>81 / 2(1) ( </em>√<em>81 = 9)</em><em>
x = -9 + 9 / 2 and x = -9 -9 /2
x = 0 and x = -18 /2 = -9
now there are two values for x one is- 9 and other is 0
so we put -9 as the value of x then answer will be zero..</em>